2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610118
|View full text |Cite
|
Sign up to set email alerts
|

Phase synchrony in subject-specific reactive band of EEG for classification of motor imagery tasks

Abstract: Recent works on brain functional analysis have highlighted the importance of distributed functional networks and synchronized activity between networks in mediating cognitive functions. The network perspective is fundamental to relate mechanisms of brain functions and the basis for classifying brain states. This work analyzes the network mechanisms related to motor imagery tasks based on synchronization measure (PLV (phase-locking value)) in EEG alpha-band for the BCI Competition IV Data Set. Based on network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…When the oscillatory phases from two brain regions are correlated the phase synchronization appears. The phase synchronization from the motor imagery period is different from the phase synchronization in the relaxation period so it can be exploited by BCI applications [17].…”
Section: Datasets Descriptionmentioning
confidence: 99%
“…When the oscillatory phases from two brain regions are correlated the phase synchronization appears. The phase synchronization from the motor imagery period is different from the phase synchronization in the relaxation period so it can be exploited by BCI applications [17].…”
Section: Datasets Descriptionmentioning
confidence: 99%
“…However, studies that used EEG-based BCIs for lower limb rehabilitation by performing MI tasks did not report, to the best of our knowledge, how brain regions connect amongst themselves. The cortical connectivity analysis describes the interactions between brain locations through patterns that represent the dynamics of information flow [ 34 , 36 , 37 ]. Thus, this information may contribute to developing more effective therapy with BCIs by obtaining a classification model based on connectivity from various subjects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, single-channel alpha enhancement with theta crossover can be achieved in less than 30-minute sessions (Demos, 2005). Recently, it has been shown that not only spectral power in different frequency bands, but also coherence and phase synchronization measures between different electrodes, can be used as NFB features (Brunner et al, 2006;Gonuguntla et al, 2013;Gysels and Celka, 2004;Sacchet et al, 2012;Wei et al, 2007). In coherence training, participants are reinforced when correlation or coupling between signals at different brain sites is altered in a desired way.…”
Section: Introductionmentioning
confidence: 99%